Fundamentals of Biomechanics : Equilibrium, Motion, and Deformation - Özkaya, Nihat (Springer New York, 1999)
Biomechanics applies the principles and rigor of engineering to the mechanical properties of living systems. This book integrates the classic fields of mechanics--statics, dynamics, and strength of materials--using examples from biology and medicine. Fundamentals of Biomechanics is excellent for teaching either undergraduates in biomedical engineering programs or health care professionals studying biomechanics at the graduate level. Extensively revised from a successful first edition, the book features a wealth of clear illustrations, numerous worked examples, and many problem sets. The book provides the quantitative perspective missing from more descriptive texts, without requiring an advanced background in mathematics. It will be welcomed for use in courses such as biomechanics and orthopedics, rehabilitation and industrial engineering, and occupational or sports medicine.